Optimal Raw Material Inventory Analysis Using Markov Decision Process with Policy Iteration Method - Ikhsan Maulidi; Radhiah Radhiah; Chintya Hayati; Vina Apriliani (Universitas Muhammadiyah Mataram, 2022)
Inventory of raw materials is a big deal in every production process, both in company production and home business production. In order to meet consumer demand, a business must be able to determine the amount of inventory that should be provided. The purpose of this research is to choose an alternative selection of ordering raw materials that produce the maximum amount of raw materials with minimum costs. The raw material referred to in this study is pandan leaves used to make pandan mats. Analysis of raw material inventory used in this research was the Markov decision process with the policy iteration method by considering the discount factor. From the analysis conducted, it is obtained alternative policies that must be taken by producers to meet raw materials with minimum costs. The results of this study can be a consideration for business actors in the study location in deciding the optimal ordering policy that should be taken to obtain the minimum operational cost.